Implementation Of Religious Moderation Values In Pai Learning At Shofiyatul Huda Junior High School - Adi Rosadi; enoh enoh; Dede Ahmad Ramdani; Uus Ruswandi; Bambang Samsul Arifin (At-Tarbiyat, 2023)
The purpose of this study was to determine the implementation of the implementation of religious moderation values in pai learning in secondary schools. This research uses a qualitative approach while the method used is descriptive. The data collection techniques were carried out through observation, interviews, and documentation. The research location is focused on the NU Shofiyatul Huda Junior High School class. The research subjects were the teacher and the Principal. Data analysis is done by selecting and sorting the answers to the data obtained then collected to be analyzed and conclusions drawn. The data analysis used is using data triangulation. The data validity test uses the stages of credibility, transferability, dependability, and confirmability. This study found that the Implementation of Religious Moderation Values at NU Shofiyatul Huda Junior High School was carried out by PAI teachers with the support of the school principal. This includes teaching the values of religious moderation, creating an inclusive environment, and strengthening tolerance. Synergy with other subjects and observed teacher practices support this endeavor. This implementation aims to form a moderate and tolerant young generation. The implementation of religious moderation values at NU Shofiyatul Huda Junior High School involves the cooperation of PAI teachers and support from the principal to create a moderate and inclusive education. Supporting factors are adequate resources and cooperation with other subjects. The obstacles are the difficulty of reaching all students and pressure from outside the school.